PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID TENTANG PRINSIP DASAR ANIMASI DENGAN METODE LUTHER-SUTOPO: DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA FOR CLASS XI MULTIMEDIA SMKN 40 JAKARTA USING LUTHER-SUTOPO METHOD - Akbar Dwipangga; M. Ficky Duskarnaen; Hamidillah Ajie (LPPM Universitas Abdurrab, 2024)
A good, creative, and interesting learning media can increase students’ interest in learning. A good learning media can also make easier for teacher to deliver material to students. Unfortunately, in the Basic Principles of Animation material in class XI Multimedia SMKN 40 Jakarta, students have difficulty accepting and understanding the material because the learning media is less attractive and the delivery is monotonous by teacher. To overcome this problem, the development of learning media in the form of Android-based applications for the Basic Principles of Animation material uses the Luther-Sutopo method which produces an Android-based application which is expected to help students understand the material. Product feasibility testing was carried out by material experts with a feasibility level of 100% with the feasibility category